2010
DOI: 10.4269/ajtmh.2010.09-0595
|View full text |Cite
|
Sign up to set email alerts
|

Survey for Tick-Borne Zoonoses in the State of Espirito Santo, Southeastern Brazil

Abstract: Blood samples collected from 201 humans, 92 dogs, and 27 horses in the state of Espirito Santo, Brazil, were tested by polymerase chain reaction, indirect immunofluorescence assays, and indirect enzyme-linked immunosorbent assay for tick-borne diseases (rickettsiosis, ehrlichiosis, anaplasmosis, borreliosis, babesiosis). Our results indicated that the surveyed counties are endemic for spotted fever group rickettsiosis because sera from 70 (34.8%) humans, 7 (7.6%) dogs, and 7 (25.9%) horses were reactive to at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 41 publications
3
28
0
11
Order By: Relevance
“…(4.4%) when compared to previous serological studies performed in dogs from endemic areas in the State of São Paulo that reported a seropositivity between 31.3 and 69.6% (LEMOS et al, 1996;HORTA et al, 2004HORTA et al, , 2007PINTER et al, 2008;MORAES-FILHO et al, 2008), from endemic areas of the State of Minas Gerais (13.7 and 81.3%) (LEMOS et al, 1994;VIANNA et al, 2008) and from endemic areas of the State of Espírito Santo (7.6%) (SPOLIDORIO et al, 2010). The seroprevalence found in the present study was also lower than that reported in dogs from non-endemic areas, 12.9% (LEMOS et al, 1996) and 20% (HORTA et al, 2007) in the State of São Paulo, and 11 to 23% in Northern Paraná (TAMEKUNI, 2009).…”
Section: Discussionmentioning
confidence: 80%
“…(4.4%) when compared to previous serological studies performed in dogs from endemic areas in the State of São Paulo that reported a seropositivity between 31.3 and 69.6% (LEMOS et al, 1996;HORTA et al, 2004HORTA et al, , 2007PINTER et al, 2008;MORAES-FILHO et al, 2008), from endemic areas of the State of Minas Gerais (13.7 and 81.3%) (LEMOS et al, 1994;VIANNA et al, 2008) and from endemic areas of the State of Espírito Santo (7.6%) (SPOLIDORIO et al, 2010). The seroprevalence found in the present study was also lower than that reported in dogs from non-endemic areas, 12.9% (LEMOS et al, 1996) and 20% (HORTA et al, 2007) in the State of São Paulo, and 11 to 23% in Northern Paraná (TAMEKUNI, 2009).…”
Section: Discussionmentioning
confidence: 80%
“…For these reasons, physicians must be aware to distinguish BYS from autoimmnune diseases. Additionally, we have found anemia, leucopenia, thrombocytopenia, transaminases increase and bilirrubinemia, mainly in BYS patients suspected of co-infections with other tick-borne diseases like babesiosis, ehrlichiosis, bartonellosis and rickettsiosis 7,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Although antibody detection may be of limited value for early serologic diagnosis (van ANDEL et al 1998), strong serological cross-reactions between all members of the A. phagocytophilum have been communicated (DUMLER et al, 1995). Recently, Spolidorio et al (2010) showed that 25.9% horses from the State of Espirito Santo, Brazil were reactive to at least one of the six Rickettsia species tested, and in six horses PCR Theileria were detected. It is important to note that no ticks of Ixodes ricinus, a common transmitter of EGA, have been described in Brazil.…”
Section: Discussionmentioning
confidence: 99%